The Principal Management in Implementing Islamic School Culture at SMAN Unggul Tunas Bangsa, Southwest Aceh - Juanda, Arisman; Yusrizal, Yusrizal; Usman, Nasir (FKIP Universitas Lampung, 2021)
The purpose of this research is to understand the plan, implementation, supervision and evaluationin implementing Islamic school culture. This research uses descriptive method with qualitative approach. Data collection were conducted through interviews,observations, and documentation studies. The subjects of this research are principal, religion teacher, homeroom teacher of grade X, XI, XII, and president of student council as student representative. The results of this research shows islamic school cultural planning is planned in school meetings, special programs concerning religious events, clean Friday group schedules, homeroom notes, making rewards and punishments. Implementation by providing motivation to students, support, commitment and cooperation in school equipment so that it can be implemented properly. Supervision is carried out jointly such as the existence of representatives of principals who help, teachers, homeroom teachers and this supervision is carried out every day. The results of the evaluation carried out showed that there was a development of students’ awareness in carrying out Islamic culture in schools, and also that there were still violating students who had not fully implemented this Islamic school culture. Keywords: principal management, culture, islamic school. DOI: 10.23960/jpp.v11.i2.202121